FACTORS INFLUENCING IMPLEMENTATION OF COMMUNITY POLICING IN NAIROBI COUNTY, KENYA - Awino, Peter Omolo; Kimani, Dr J. M. (Journal of Public Policy and Administration, 2017)
Purpose: The overall research objective sought to determine the organizational logistics, police attitudes and community commitment that influence the effective implementation of Community Policing within Nairobi County in Kenya. Methodology: The research adopted a descriptive research design using both quantitative and qualitative approaches. The target population was 2,883 police officers and 985,016 households from which samples of 384 households and 339 police officers were drawn Data collection was carried out using Research Questionnaires and Focus Group Discussions. Data collected was analyzed through quantitative and qualitative techniques based on descriptive statistics where mode, frequency tables, bar graphs, and percentages were used to describe and present the data based on each research objective. Pearson's correlation analysis was used for testing the research hypotheses and measuring of relationships. Results: The study established that the police were far from the expectation of the community and apart from the community commitment; police attitudes and organizational logistics were identified as factors influencing the implementation of COP in Nairobi. Conclusion: The study recommends that the community should be educated on community policing initiatives; monitoring the role of police in the community; and how to manage community commitment that influences the implementation of COP in Nairobi County. Policy recommendation: The findings of this research study will be useful to stakeholders such as the Government of Kenya, the police department and the community in Nairobi in guiding policy and strategy formulation aimed at enhancing the quality of community policing implementation. Keywords: Community policing: organization logistics, COP implementation